2002
DOI: 10.1046/j.1469-0691.2002.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between Bartonella DNA detection within fleas, serological results, and results of blood culture in a Bartonella-infected stray cat population

Abstract: The lack of correlation between Bartonella DNA detection within fleas, serological results, and results of blood culture is probably due to a lack of natural heterologous protection between species or serotypes. Cats suffer bacteremia with three Bartonella species and should therefore be considered the reservoirs of at least three human pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
3
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 35 publications
5
42
3
3
Order By: Relevance
“…First, non-infected rodents hosted infected fleas, and infected rodents carried negative fleas. This lack of correlation between infected and non-infected individuals was previously observed (La Scola et al, 2002;Brinkerhoff et al, 2010;Billeter et al, 2011). Second, when the Bartonella infection at a genotype level was analyzed, a clear trend of some genotypes to dominate a particular niche was revealed.…”
Section: Discussionmentioning
confidence: 51%
“…First, non-infected rodents hosted infected fleas, and infected rodents carried negative fleas. This lack of correlation between infected and non-infected individuals was previously observed (La Scola et al, 2002;Brinkerhoff et al, 2010;Billeter et al, 2011). Second, when the Bartonella infection at a genotype level was analyzed, a clear trend of some genotypes to dominate a particular niche was revealed.…”
Section: Discussionmentioning
confidence: 51%
“…In humans, B. henselae seroprevalence ranges between 5.7% in healthy human blood donors [52] and up to 87% in human patients with suspected cat scratch disease [57]. Cats appear to be the main reservoir of B. henselae infection as indicated by the high seroprevalences found in cats worldwide [7] as well as documentation of persistent bacteremia in naturally and experimentally infected cats [1,40,43]. Bacteremia has been infrequently documented in dogs, and only by PCR amplification [6,51].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it would be reasonable to hypothesize that antibodies against the antigens of B. henselae type II might not reacted with the antigens of B. henselae type I. Previous reports [11,21] have also shown that cats with B. henselae type II or B. clarridgeiae bacteremia could Sero-negative but PCR-positive 2 12…”
mentioning
confidence: 99%